Automation and Scale Up of Somatic Embryogenesis for Commercial Plant Production, With Emphasis on Conifers - Egertsdotter, Ulrika; Ahmad, Iftikhar; Clapham, David (Frontiers in Plant Science, 2019)
For large scale production of clonal plants, somatic embryogenesis (SE) has many advantages over other clonal propagation methods such as cuttings. In particular, the SE process is more suited to scale up and automation, thereby reducing labor costs and increasing the reliability of the production process. Furthermore, the plants resulting from SE closely resemble those from seeds, as somatic embryos, like zygotic (seed) embryos, develop with good connection between root and shoot, and without the plagiotropism often associated with propagation by cuttings. For practical purposes in breeding programs and for deployment of elite clones, it is valuable that a virtually unlimited number of SE plants can be generated from one original seed embryo; and SE cultures (clones) can be cryostored for at least 20 years, which is important for conifers with long generation times. To date, there has however been limited use of SE for large-scale plant production mainly because without automation it is labor-intensive. Development of automation is particularly attractive in countries with high labor costs, where conifer forestry is often of great economic importance. Various approaches for automating SE processes are under investigation and the progress is reviewed here, with emphasis on conifers. These approaches include simplification of culture routines with preference for liquid rather than solid cultures, use of robotics and automation for singulation and harvest of selected mature embryos, followed by automated handling of germination and subsequent planting. Here automation and scale up efforts for SE plant production are reviewed with the focus on conifers as one of the globally most significant targets for automation and scale up efforts of in vitro plant production. Different approaches to handle the processes of somatic embryogenesis in conifers are outlined below, followed by an update on efforts to automate the different steps.